Analisis Pemahaman Terhadap Akuntansi Syariah Berdasarkan PSAK 107 Pada PT. Pegadaian Syariah CPS Rantau Prapat - Ananda Putri Azni Mtd; Fauzi Arif Lubis; Rahmat Daim Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
PSAK 107 regulates recognition, measurement, presentation and disclosure and Ijarah transactions are contracts for the transfer of use rights (benefits) of an asset within a certain time with rental payments (ujrah) without being followed by a transfer. There are differences in understanding regarding the sharia accounting system, especially in PSAK 107 regarding employees of PT. Pegadaian Syariah CPS Rantau Prapat, there are significant differences in majors for each employee graduate, thereby closing job opportunities for those who match their major. This research aims to find out to what extent employees understand sharia accounting records based on PSAK 107 at PT. CPS Sharia Pawnshop located in the city of Rantau Prapat, Labuhan Batu Regency, North Sumatra Province. This research method is qualitative research and this research approach uses descriptive qualitative. The final results of the qualitative descriptive show that employees' understanding of pawn contracts based on PSAK107 falls into the category of very understanding through interviews and direct observations with researchers who have been studied at the level of the cognitive domain of the pyramid of understanding which states that a person understands if he can explain it again in his own language. what he heard was appropriate and all transactions were clearly recorded and journalized and the presentation of financial reports at PT. Pegadaian Syariah CPS Rantau Prapat was in accordance with PSAK 107.